2017
DOI: 10.1080/14786419.2017.1324962
|View full text |Cite
|
Sign up to set email alerts
|

A new oxo-sterol derivative from the rhizomes of Costus speciosus

Abstract: Chemical investigation of the rhizomes of Costus speciosus led to the isolation of a new compound, 22-ketocholesteryl palmitate (1) along with four known compounds, 24-methylenecycloartanol (2), cycloartanol (3), stigmasterol (4) and linoleic acid (5). The structure of new compound was characterised by extensive 1D-, 2D-NMR and mass spectrometry (GC-MS and HR-ESI-MS) techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Fatty Acid: Hexadecanoic acid, 9, 12 octadecanoic acid, tetradecanoic acid, and oleic acid can enhance insulin production in INS-1. 52 TNF-alpha inhibits insulin production but pre-treatment with oleic acid reverses the inhibitory activity. Thus glucose level is decreased.…”
Section: Proteinsmentioning
confidence: 99%
“…Fatty Acid: Hexadecanoic acid, 9, 12 octadecanoic acid, tetradecanoic acid, and oleic acid can enhance insulin production in INS-1. 52 TNF-alpha inhibits insulin production but pre-treatment with oleic acid reverses the inhibitory activity. Thus glucose level is decreased.…”
Section: Proteinsmentioning
confidence: 99%
“…The diuretic index values of rhizome extract at a dose of 200 mg/kg and 400 mg/kg were 3.25, 1.25, respectively, indicating a weak diuretic activity of the extract compared with furosemide standard. Lijuan et al reported that 10 mg/100 mL rhizome extract of C. speciosus stimulates urination properties in rats [20].…”
Section: Diuretic Activitymentioning
confidence: 99%
“…Department of Agriculture, 2016). Updated findings of each plant species were also referred (Al-Snafi, 2018;Bagalkotkar et al, 2006;El-far AH, Shaheen, HM, Alsenosy, AW, El-Sayed YS, Al Jaouni SK, Mousa, 2018;Jadhav et al, 2009;Kamruzzaman and Hoq, 2016;Kumar et al, 2018bKumar et al, , 2018aMissoum, 2018;Mohamad et al, 2018;Narendra et al, 2012;Pawar and Pawar, 2014;Qiao et al, 2002;Rani et al, 2012;Salem et al, 2014;Thabit, 2018;Thambi and Shafi, 2015;Waisundara et al, 2015) and compiled into a list of compounds (Supplementary Table 1). Compounds that do not possess the canonical simplified molecular-input line-entry system (SMILES) in PubChem were removed.…”
Section: Prediction Of Bioactive Compounds and Target Genesmentioning
confidence: 99%